2022
DOI: 10.1021/acsomega.1c05823
|View full text |Cite
|
Sign up to set email alerts
|

Composite Graphite–Epoxy Electrodes for In Situ Electrochemistry Coupling with High Resolution NMR

Abstract: The in situ coupling between electrochemistry and spectrometric techniques can help in the identification and quantification of the compounds produced and consumed during electrochemical reactions. The combination of electrochemistry with nuclear magnetic resonance is quite attractive in this respect, but it has some challenges to be addressed, namely, the reduction in the quality of the NMR signal when the metallic electrodes are placed close to or in the detection region. Since NMR is not a passive technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…However, when the electrodes were positioned 1 cm within the region, the obtained FWHM was 1.43 Hz. Comparing these values with those obtained with metallic electrodes published in other works, , it is observed that the distortion caused by our carbon fiber paper electrodes is significantly lower. To obtain a quantitative spectrum, it is necessary that the standard peak has a FWHM of approximately 1 Hz.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, when the electrodes were positioned 1 cm within the region, the obtained FWHM was 1.43 Hz. Comparing these values with those obtained with metallic electrodes published in other works, , it is observed that the distortion caused by our carbon fiber paper electrodes is significantly lower. To obtain a quantitative spectrum, it is necessary that the standard peak has a FWHM of approximately 1 Hz.…”
Section: Resultsmentioning
confidence: 99%
“…The position of the electrodes relative to the detection region was evaluated, and Figure shows the comparison between the spectra in the main regions of interest of the NMR spectrum of the AA when the electrodes were positioned 1 mm above the detection region (black line) and 1 cm within the detection region (red line). For more details on the placement of the electrodes see the work of da Silva et al published in 2022 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations